Biomechanical characteristics related to poling propulsive effectiveness in cross-country V2 skating technique - Bessone, V.; Paternoster, F.; Stanglmeier, M.; Veith, M.; Schuster, R.; Schwirtz, A.; Seiberl, W. (ISBS Proceedings Archive (Michigan), 2017)
The purpose of this study was to investigate whether specific kinetic and kinematic characteristics distinguish the propulsive effectiveness of upper body in V2 cross-country skating technique. Female and male skiers (n=25) performed V2 on a treadmill using roller skis at a 6% incline, while kinetic parameters of plantar pressure and ski pole forces, as well as 3d-kinematic data were collected. The ratio between propulsive and overall impulse (effectiveness) of ski poles was 50% for female and 52% for male athletes and highly correlated with ski pole angles. Male skiers showed smaller pole angles at maximum propulsive force than females (P<0.05). Athletes should consider a more effective ski pole planting angle in order to improve propulsive poling action and consequently their performance.